The Effect of the Addition of Graphene Nanoplatelets on the Selected Properties of Cementitious Composites - Ge, Zhi; Qin, Jin; Sun, Renjuan; Guan, Yanhua; Zhang, Hongzhi; Wang, Zheng (Frontiers in Built Environment, 2021)
The aim of the current study is to investigate the properties of graphene nanoplatelets-cement composites in a consistent sense. The influence of the addition of 2D graphene nanoplatelets (GNPs) on the workability, setting time, flowability, strengths and pizozresistive properties were studied. The dosage of the GNPs is 0 0.05, 0.1, 0.3, 0.5, 0.7, 1.0 wt% of the binder material. PVP type surfactant was used to disperse GNPs. The experimental results showed that the addition of GNPs increases the water requirement for normal consistency and decreases the flowability. A small amount of GNPs (0.05 wt%) can facilitate the setting. When the dosage of GNPs is above 0.1 wt%, it leads to the delay of the setting time. In terms of the strengths, the addition of GNPs can considerably promote the flexural strength, while the compressive strength is slightly decreased until 28 days. A pre-treatment procedure consists of drying specimens at 105 °C for 1 day can be regarded as a proper way to enhance the pizozresistive properties of the GNPs-mortar. Pizozresistive properties under two different cyclical loading schemes were measured using the GNPs-mortar with 1 % GNPs. It has been shown that the average resistance change rate increases with the amplitude increasing and a reduction is observed for the sustained cyclical loading condition. In the end, the influence of the microcracks on the pizozresistive properties was investigated. This study will contribute to future developments of cementitious composites incorporating GNPs for a variety of applications.